PENYULUHAN DAN SOSIALISASI DIASTASIS RECTI ABDOMINIS DI POSYANDU DAHLIA 4 DESA LEWO BARU MALANGBONG GARUT - Naning Suryani; Elang Mohamad Atoilah; Intan Rina Susilawati; Tri Wahyuni (Jurnal Pengabdian Masyarakat DEDIKASI, 2020)
The incidence of diastasis recti abdominis is reported to be higher during the third trimester of pregnancy and immediately after delivery. International literature shows the prevalence value of diastasis recti abdominis is between 35%-100%. Most women with positive diastasis recti abdominis aged between 26-35 years. The risk factors for diastasis recti abdominis are hormonal changes in pregnancy, increased uterine size, anterior pelvis with or without lumbar hyperlordosis, increased intra-abdominal cesarean section, multiple pregnancies, fetal macrosomia, and genetic defects in collagen structure including congenital disproportion of the collagen ratio III. or I, substantial loss of body mass spontaneously or after bariatric surgery, abdominal surgical procedures.